2023
DOI: 10.3390/life13030613
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Positive Airway Pressure Reduces Plasma Neurochemical Levels in Patients with OSA: A Pilot Study

Abstract: Obstructive sleep apnea (OSA) is a risk factor for neurodegenerative diseases. This study determined whether continuous positive airway pressure (CPAP), which can alleviate OSA symptoms, can reduce neurochemical biomarker levels. Thirty patients with OSA and normal cognitive function were recruited and divided into the control (n = 10) and CPAP (n = 20) groups. Next, we examined their in-lab sleep data (polysomnography and CPAP titration), sleep-related questionnaire outcomes, and neurochemical biomarker level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…A similar study by Liu et al [42] compared plasma biomarkers Aβ42 and T-tau in PAP and non-PAP OSAHS patients. Those using PAP treatment demonstrated a significantly reduced level of both biomarkers compared to the non-PAP group after 3 months of treatment.…”
Section: Effect Of Positive Airway Pressure Treatment On Levels Of Bi...mentioning
confidence: 94%
See 1 more Smart Citation
“…A similar study by Liu et al [42] compared plasma biomarkers Aβ42 and T-tau in PAP and non-PAP OSAHS patients. Those using PAP treatment demonstrated a significantly reduced level of both biomarkers compared to the non-PAP group after 3 months of treatment.…”
Section: Effect Of Positive Airway Pressure Treatment On Levels Of Bi...mentioning
confidence: 94%
“…Search term PubMed ("Mild cognitive impairment" OR "cognitive decline" OR "cognitive dysfunction" OR "mild cognitive deficit" OR "Alzheimer disease" OR AD OR amyloid OR "MCI" OR "amnestic mild cognitive impairment" OR "degenerative disease" OR "amyloid precursor protein A total of 45 studies were found. Of the 45, 15 studies discussed the hypothesised glymphatic system in relation to sleep [11,12,[23][24][25][26][27][28][29][30][31][32][33][34][35], 5 studies assessed the impact of PAP on brain fluid diffusivity in patients with OSAHS [36][37][38][39][40], 4 studies assessed the influence of PAP treatment on the level of AD biomarkers [29,31,41,42], 11 studies measured the impact of PAP treatment on cognitive function in OSAHS [1,4,14,[43][44][45][46][47][48][49][50] and 10 studies measured the impact of PAP treatment on cognitive function in OSAHS and aMCI/AD [7,8,17,20,21,[51][52][53][54]…”
Section: Databasementioning
confidence: 99%